SEASONAL VARIATION IN DISSOLVED CARBOHYDRATE (DCHO) CONTENT IN THREE FRESHWATER PONDS - Vijayaraghavan, Sumitra (Indian Journal of Fisheries, 2011)
Considerable work has Been done on the dynamics of DCHO from temperateregions. Some of the contributions are those of Allen (1956) Guillard andWangersky (1958), Nalewajo et al. (1963) and Walsh (1965 and 1966). However,practically no information is available on this important constituent fromthe tropics. Fogg (1962) stated that the rate of turnover of organic acids andcarbohydrates is probably high enough to Ue ecologically important. In thepresent paper, therefore, an attempt has been made to study the seasonal variationsin DCHO in relation to some of the physico-chemical and biologicalfactors in three tropical ponds.